Pembelajaran Matematika Berbasis Masalah dengan Strategi Inkuiri Terbimbing dan Inkuiri Bebas Termodifikasi Ditinjau dari Kemampuan Awal Siswa MTs - Cahyani, Eko Diah (Jurnal VARIDIKA, 2016)
The purposes of this study are (1) to test the effect difference of problem based learning strategies guided inquiry and modified free inquiry on student learning outcomes, to (2) test the effect difference early ability categories of high, medium and low student to student learning outcomes, and (3) Â to test the interaction between early ability category strategy with high, medium and low student to student learning outcomes. This type of research is quantitative with quasi experiment Desain. The population are all students of class VII MTs Tamirul Islam Surakarta. The research sample two classes. The sampling technique is cluster random sampling by lottery. Data collection techniques used cognitive testing and documentation. Data were analyzed using analysis of variance of two different cell. The results of the study with Î± = 5%. The results are (1) there are differences in the effect of problem-based learning strategies guided inquiry and modified free inquiry on student learning outcomes, (2) there are differences in the effect of the initial capabilities categories of high, medium and low student to student learning outcomes, and (3) there is no interaction between early ability category strategy with high, medium and low student to student learning outcomes